Ivan Pesin (to his 90th anniversary) - M. Zarichnyi; L. Bazylevych; I. Oleksiv; Ya. Prytula (Математичні Студії, 2020)
The note is devoted to biography and achievements of Ukrainian mathematician Ivan Pesin (1930--1993).